Population structure, connectivity and ecological dynamics of the Antarctic silverfish, Pleuragramma antarctica - Caccavo, Jilda Alicia (Università degli studi di Padova, 2018)
The Antarctic silverfish (Pleuragramma antarctica) is a keystone species in the continental shelf waters around the Antarctic, performing an essential role of connecting higher and lower trophic levels in the Southern Ocean ecosystem. Its early life history is dependent on the platelet ice layer found below sea ice, thus intimately intertwining its fate with that of sea ice extent. Antarctic silverfish belong to the family Nototheniidae, part of the Notothenioidei suborder whose species radiation in the Southern Ocean 24 million years ago is one of the most expansive among teleost fish. Most notothenioids inhabit a benthic niche as adults, though many experience a pelagic egg and larval phase. Antarctic silverfish are unique among notothenioids in that they are pelagic throughout their life history. Larvae develop in the platelet ice layer near the surface beneath sea ice, descending into deeper waters as they grow in size as juveniles, finally reaching their maximum depth range as adults at 400 – 700 m below the surface. While they lack a swim bladder, Antarctic silverfish manage to remain in the water column as adults by a type of paedomorphy in which they retain lipids from larval and juvenile life stages, allowing them to achieve neutral buoyancy. Despite their presence in the water column as adults, they practice a similar energy-efficient life strategy to their benthic counterparts. Their feeding strategy involves hanging in the water column and passively consuming prey. Remaining in the water column throughout their life history combined with their passive life strategy renders Antarctic silverfish especially susceptible to transport via local and circumpolar current systems. Thus, local and circumpolar current systems form the hydrographic framework in which hypotheses regarding Antarctic silverfish population connectivity must be tested. How populations of fish are defined, and the extent to which separate populations exchange individuals forms the basis of marine fish population biology. The extent to ...